Makna Dhiya dan Nur dalam Qur’an Surah Yunus: 5 Menurut Tafsir Zubdatut Tafsir Min Fathil Qadir - Rambe, Putri Chairani (YASIN, 2023)
This research is entitled The Meaning of Dhiya and Nur in the Qur'an Surah Yunus Verse 5 According to Tafsir Zubdatut Tafsir Min Fathil Qadhir. Dhiya and Nur are celestial bodies that have extraordinary uniqueness and benefits for life in the world. The sun in the Qur'an is called the word ash-Sham, which is symbolized as dhiya' and siraj. Both have the same meaning, namely that they both explain that the source of the sun's energy comes from itself and the light that emerges from the sun functions as a shadow light. The purpose of this research is to find out the meaning of dhiya and nur in the Qur'an surah Yunus verse 5 according to Tafsir Zubdatut Tafsir Min Fathil Qadir. As well as knowing how the meaning of dhiya and nur is in terms of theoretical language and its relation to the verses of the Qur'an. In this study using qualitative methods, the type is library research (library research), namely efforts to obtain data in the literature. Namely studying books related to existing problems with the discussion discussed in this thesis. Based on data analysis research, this study uses the interpretation approach theory. The interpretation research approach is the science of understanding the Book of Allah revealed to the Prophet of Allah. In this case the authors classify sources into two categories, namely primary sources and secondary sources. The results of this study are; That in the Qur'an surah Yunus verse 5 explains that Allah mentions the sun and the moon with different names. In this verse, the sun is called dhiya and the moon is called nur.)